2016
DOI: 10.3831/kpi.2016.19.014
|View full text |Cite
|
Sign up to set email alerts
|

Inductions of Caspase-, MAPK- and ROS-dependent Apoptosis and Chemotherapeutic Effects Caused by an Ethanol Extract of Scutellaria barbata D. Don in Human Gastric Adenocarcinom Cells

Abstract: Objectives:The crude extracts of Scutellaria barbata D. Don (SB) have traditionally demonstrated inhibitory effects on numerous human cancers both in vitro and in vivo. Gastric cancer is one of the most common types of cancer on world. The authors investigated the effects of an ethanol extract of Scutellaria barbata D. Don (ESB) on the growth and survival of MKN-45 cells (a human gastric adenocarcinoma cell line).Methods:The MKN-45 cells were treated with different concentrations of ESB, and cell death was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…SB inhibits Calu-3 cell growth via suppression of the HER2 pathway and angiogenesis [ 28 ]. SB induces A549 cell apoptosis through the intrinsic mitochondrial pathway [ 58 ]. In our in vitro study, SB-induced CL1-5 cell death occurred through multiple pathways, including the intrinsic mitochondrial-, extrinsic death receptor-, and ER stress-mediated apoptosis pathways, as well as through cell cycle arrest and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…SB inhibits Calu-3 cell growth via suppression of the HER2 pathway and angiogenesis [ 28 ]. SB induces A549 cell apoptosis through the intrinsic mitochondrial pathway [ 58 ]. In our in vitro study, SB-induced CL1-5 cell death occurred through multiple pathways, including the intrinsic mitochondrial-, extrinsic death receptor-, and ER stress-mediated apoptosis pathways, as well as through cell cycle arrest and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Its polysaccharide, iridoids, and sfingolipids compositions have significant antitumor effects on the GC [ 14 , 15 ]. The study has shown that the ethanol extract of Scutellaria barbata induces apoptosis through Caspase-, MAPK-, and ROS-dependent pathways, and it exerts chemotherapeutic effects in human gastric adenocarcinoma cells [ 16 ]. Therefore, it is of great interest to explore the therapeutic effects and potential molecular mechanisms of modified GZT in GC.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance in the production and consumption of reactive oxygen species (ROS) leads to oxidative stress in cells. Oxidative stress biomarkers (including ROS, nitric oxide (NO), malondialdehyde (MDA), and superoxide dismutase (SOD)) can reflect the degree of cell oxidative damage [ 11 13 ]. Therefore, it is necessary to adopt effective antioxidant strategies to reduce the production of ROS, thereby preventing oxidative damage caused by CVC.…”
Section: Introductionmentioning
confidence: 99%